Evaluasi Kualitas Website Dinas Pemerintah Daerah Kabupaten Ogan Komering Ulu Menggunakan Metode Webqual 4.0 - Didik Aripin (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
The website has become an important part of government matters for government agencies. To find out the level of satisfaction of website users need to be considered in order to be an assessment for website managers. In this evaluation process the writer uses the webqual method and guidelines for administering a web site from the government. In the process of data analysis, researchers invited a questionnaire using the purposive sampling method, and the number of respondents was 30 people, with the analysis completing the validity and reliability testing. Furthermore, the questionnaire data was processed according to the distribution of respondents produced by the OKU Disdukcapil website received a good response from respondents with a yield rate of 65.83%. Then the website that is in accordance with the Government Guidelines with the Disdukcapil OKU website results with a percentage of conformity level of 62.06%.Keywords: website, webqual, usability